Entwicklung und Realisierung einer Modellbibliothek für ein Entscheidungsunterstützungssystem in der Kalksandsteinproduktion - Schrage, Tobias; Schuderer, Peter; Barth, Martin; Franke, Jörg (20. ASIM Fachtagung Simulation in Produktion und Logistik 2023, 2023)
The digitization in the context of the fourth industrial revolution provides new opportunities for value chains and the optimal design of production. Simulation is discussed as a valuable tool for production planning and control in cases where modeling and analysis require significant computational effort. Simulation helps determine production times and costs under varying buffer sizes, machine performance, cycle times, and batch sizes, as they are present for calcium silicate brick production. Meanwhile, energy is increasingly becoming a factor in the resourceoriented management of companies. In case of resource-oriented production planning and control is becoming a survival factor. Therefore, for a simulation-based decision support system for production planning in the calcium silicate brick industry, a model library for material flow simulation is extended and tested based on 5 reference plants.<br